Oligosaccharides mapping of nitrous acid degraded heparin through UHPLC-HILIC/WAX-MS. (1st March 2020) - Zhang, Tianji; Xie, Shaoshuai; Wang, Zhangjie; Zhang, Rui; Sun, Qianyun; Liu, Xin; Chi, Lianli; Li, Jin-ping; Li, Hongmei; Tan, Tianwei
Highlights: Application of a LC–MS method for mapping HONO depolymerized heparin oligosaccharides. Characterization of 19 tetra-, 19 tri- and 4 mono-saccharides. Identification of special oligosaccharide signatures and "end" structures of heparin. Abstract: Building blocks characterization is a significant approach for understanding the molecular structure of heparin and its derivatives. Nitrous acid (HONO) depolymerization of heparin generates oligosaccharides that maintain the epimerization conformation on C5 of the uronic acids, reflecting the authentic structure of the parental chain. HONO treatment at pH 1.5 selectively cleaves the bond between N-sulfated glucosamine and hexuronic acid, resulting mainly disaccharides, as well as tetra-, tri-, and mono-saccharides. The tetrasaccharides are derived from the structure of N-acetylated domains while tri-, and mono-saccharides are derived from the reducing or the non-reducing end of the heparin chain. The resulted oligosaccharides were separated and analyzed using a UHPLC-HILIC/WAX-MS method. We succeeded in the identification of 19 tetrasaccharides, 19 trisaccharides and 4 monosaccharides species, majority of which is structurally characterized. By comparing the theoretical possibilities and actual occurrence of the well-characterized tetrasaccharides, we demonstrated that the biosynthesis of heparin is a systematic process.